Non-Volatile Component and Antioxidant Activity: A Comparative Analysis between Litsea cubeba Branches and Leaves - Wei Dai; Boyi Li; Yanli Xiong; Liping Dai; Yuan Tian; Liangqian Zhang; Qi Wang; Guoqiang Qian (Molecules, 2024)
Litsea cubeba, which is found widely distributed across the Asian region, functions as both an economic tree and a medicinal plant with a rich historical background. Previous investigations into its chemical composition and biological activity have predominantly centered on volatile components, leaving the study of non-volatile components relatively unexplored. In this study, we employed UPLC-HRMS technology to analyze the non-volatile components of L. cubeba branches and leaves, which successfully resulted in identifying 72 constituents. Comparative analysis between branches and leaves unveiled alkaloids, organic acids, and flavonoids as the major components. However, noteworthy differences in the distribution of these components between branches and leaves were observed, with only eight shared constituents, indicating substantial chemical variations in different parts of L. cubeba. Particularly, 24 compounds were identified for the first time from this plant. The assessment of antioxidant activity using four methods (ABTS, DPPH, FRAP, and CUPRAC) demonstrated remarkable antioxidant capabilities in both branches and leaves, with slightly higher efficacy observed in branches. This suggests that L. cubeba may act as a potential natural antioxidant with applications in health and therapeutic interventions. In conclusion, the chemical composition and antioxidant activity of L. cubeba provides a scientific foundation for its development and utilization in medicine and health products, offering promising avenues for the rational exploitation of L. cubeba resources in the future.